BATASAN TANGGUNG JAWAB DIREKSI ATAS KERUGIAN PERUSAHAAN - Subekti, Trusto (Faculty of Law, Universitas Jenderal Soedirman, 2008)
The effect of monetary crisis in year 1997 has caused many share companies in Indonesia close down because of unprofitable. At that moment, the price of shareholder drastic downwards, even exists to the zero level and effected to the bankruptcy. For the agenda of overcoming situation of share company, many ways have been conducted by the board of directories company to overcome the loss by using the law corridor, but somehow there are many party conduct action by impinged the laws. The problems which stated here is”how far a Board of directors can be responsible to the loss suffered of the company”. From the theoretical study, it expected can be obtained the image of concerning indicator of a director that conduct the abuse of power. Keywords: share company, board of directories, and abuse of power